The Impact of Dog-Assisted Therapy Among Children and Adolescents with Autism Spectrum Disorder: A Systematic Review - Paula Galvany-López; Manuel Martí-Vilar; Sergio Hidalgo-Fuentes; Javier Cabedo-Peris (Children)
Background and Objectives: Animal-assisted therapies have been utilized in various profiles to improve people’s quality of life. This systematic review aims to assess the impact of dog-assisted therapies (DAT) on children and adolescents with Autism Spectrum Disorder (ASD). The benefits provided, the feasibility of implementation, and potential limitations are analysed. Methods: An exhaustive search was carried out in the following databases: Web of Science (WoS), Scopus, ERIC, PubMed, PubPsych, CINAHL, PsycInfo and Dialnet. The procedure was preregistered on PROSPERO. Results: This review included 19 scientific articles. Of these, 84% suggest that DAT has a positive impact on communication and social interaction during the development of children and adolescents diagnosed with ASD. The dog is often perceived as a communication facilitator that serves as a reinforcer, capturing the individual’s attention. Emotional benefits have also been reported, including reducing stereotyped and self-harming behaviours. Additionally, an increase in smiling frequency and self-esteem levels was observed. Conclusions: These findings highlight the potential of DAT as a component of socio-educational intervention for children and adolescents diagnosed with ASD. However, further research is necessary due to the limited sample sizes in the studies reviewed.